Chemical, Structural and Optical Properties of ē-Beam Evaporated Tungsten Diselenide Polycrystalline Thin Film - Mayur M. Patel; K.D. Patel; V.M. Pathak; R. Srivastava (Журнал нано- та електронної фізики)
Polycrystalline thin films of tungsten dieseline were prepared by using rarely reported technique of electron beam evaporation for transition metal dichalcogenides. High purity (99.999 %) reacted compound was used as starting material for the preparation of WSe2 thin films. Various parameters and conditions are outlined which were used for deposition of thin films. The prepared films were characterized using EDAX spectrum, X-ray diffraction, Electron diffraction, Scanning electron microscopy and optical absorption spectroscopy methods. The as grown films were found to be partially transparent, uniform and well adherent. Uniformity was confirmed by SEM. WSe2 film was found in stoichiometric proportion. XRD pattern as well as TEM images revealed the fact that the deposited films are polycrystalline in nature having hexagonal structure. From the study of optical absorption spectra it is found that the prepared films show direct allowed transition with optical band gap of 1.89 eV. The results are in good agreement with the earlier published data of WSe2 thin films deposited by different techniques.